2002
DOI: 10.1038/sj.onc.1205578
|View full text |Cite
|
Sign up to set email alerts
|

The cyclin D1 high and cyclin E high subgroups of breast cancer: separate pathways in tumorogenesis based on pattern of genetic aberrations and inactivation of the pRb node

Abstract: In an attempt to identify subtypes of breast cancer and pinpoint patterns of cell cycle regulatory defects associated with clinical behaviour, proliferation and other transformation associated events, a multitude of cell cycle regulatory proteins were analysed in a material of 113 primary breast cancers. Increased proliferation was observed in two different scenarios; (1) with high cyclin D1 and elevated retinoblastoma protein (pRb) phosphorylation, (cyclin D1 high tumours) or (2) with high cyclin E protein bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
82
0
4

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 45 publications
(78 reference statements)
7
82
0
4
Order By: Relevance
“…18,26 Proliferating cells are under the control of proteins in the cell cycle, and HIF-1a appears to be positively associated to proteins involved in S/G 2 -phase such as cyclin E and cyclin A2, but negatively associated to cyclin D1, which mainly functions in early G 1 -phase. This is in concordance with earlier published data, 35 but apart from the association to the cell cycle, this could also indicate that HIF-1a expression is correlated to a certain type of breast cancer with proliferative features and frequent overexpression of cyclin E. 36,37 HIF-1a has not been previously explored in relation to treatment prediction in a randomised treatment trial, but one breast cancer cell line study has demonstrated that hypoxia induces tamoxifen-resistant growth. 24 In our study we could not confirm this link between hypoxia and tamoxifen response, and both HIF1a low and high tumours appeared to respond to tamoxifen treatment.…”
Section: Discussionsupporting
confidence: 80%
“…18,26 Proliferating cells are under the control of proteins in the cell cycle, and HIF-1a appears to be positively associated to proteins involved in S/G 2 -phase such as cyclin E and cyclin A2, but negatively associated to cyclin D1, which mainly functions in early G 1 -phase. This is in concordance with earlier published data, 35 but apart from the association to the cell cycle, this could also indicate that HIF-1a expression is correlated to a certain type of breast cancer with proliferative features and frequent overexpression of cyclin E. 36,37 HIF-1a has not been previously explored in relation to treatment prediction in a randomised treatment trial, but one breast cancer cell line study has demonstrated that hypoxia induces tamoxifen-resistant growth. 24 In our study we could not confirm this link between hypoxia and tamoxifen response, and both HIF1a low and high tumours appeared to respond to tamoxifen treatment.…”
Section: Discussionsupporting
confidence: 80%
“…These results are particularly intriguing, since a recently published study noted a statistically significant correlation between cyclin E overexpression and decreased levels of Bcl-2 in breast tumors. 35 Overexpression of cyclin E in MCF7 cells results in a precipitous drop of Bcl-2, which is due to a decrease in mRNA levels (NKDFunpublished data). T47D cells have very low, but detectable levels of Bcl-2.…”
Section: Discussionmentioning
confidence: 99%
“…38,41,67 Most series have exhibited lower cyclin-D1 expression levels in BRCA1 than in sporadic tumors. 38,40,68 Cyclin-D1 expression in BRCA2 tumors has been found at an intermediate level between those of BRCA1 and sporadic tumors. For example, Osin et al 40 reported that cyclin D1 was expressed in 27% of BRCA2 tumors, compared with 5% in BRCA1 tumors and 35% in sporadic tumors.…”
Section: Alterations In Cell-cycle Regulationmentioning
confidence: 99%
“…These tumors had a more substantial lack of G1/S control, adopting an Rb-independent mechanism of cell proliferation. 68 …”
Section: Alterations In Cell-cycle Regulationmentioning
confidence: 99%